2020
DOI: 10.1097/iae.0000000000002808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Natural History of Rho-Associated Retinitis Pigmentosa

Abstract: Purpose: To investigate the natural history of RHO-associated retinitis pigmentosa (RP). Methods: A multicenter, medical chart review of 100 patients with autosomal dominant RHO-associated RP. Results: Based on visual fields, time-to-event analysis revealed median ages of 52 and 79 years to reach low vision (central visual field ,20°) and blindness (central visual field ,10°), respectively. For the best-corrected visual acuity (BCVA), the median age to reach mild impairment (20/67 # BCVA , 20/40) was 72 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…High myopia (refractive error of −6 diopters or more) may be associated with a more rapid disease progression, for instance in RPGR -associated X-linked RP [ 69 , 71 , 72 ]. In contrast, patients with adRP (e.g., due to RHO mutations) mostly demonstrate a relatively mild disease course compared to arRP or XLRP, and they may even retain considerable central and peripheral visual function up until the eighth decade of life [ 73 , 74 , 75 ]. The disease course of RP is best understood in the most prevalent genes associated with RP (e.g., RHO and RPGR ) as more extensive retrospective and prospective studies have been performed in these genes; thus, their visual prognosis can be more accurately estimated [ 23 , 68 , 71 , 73 , 74 , 76 , 77 , 78 ].…”
Section: Disease Onset and Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…High myopia (refractive error of −6 diopters or more) may be associated with a more rapid disease progression, for instance in RPGR -associated X-linked RP [ 69 , 71 , 72 ]. In contrast, patients with adRP (e.g., due to RHO mutations) mostly demonstrate a relatively mild disease course compared to arRP or XLRP, and they may even retain considerable central and peripheral visual function up until the eighth decade of life [ 73 , 74 , 75 ]. The disease course of RP is best understood in the most prevalent genes associated with RP (e.g., RHO and RPGR ) as more extensive retrospective and prospective studies have been performed in these genes; thus, their visual prognosis can be more accurately estimated [ 23 , 68 , 71 , 73 , 74 , 76 , 77 , 78 ].…”
Section: Disease Onset and Prognosismentioning
confidence: 99%
“…The onset and presentation of the aforementioned fundus findings differ highly between individuals and may even present in atypical forms. Sector RP is considered an atypical, mild form of RP, which is more common in patients with adRP [ 69 , 73 , 83 , 84 , 85 ]. Degeneration in sector RP has a predilection for the inferior nasal hemisphere of the retina with corresponding superior visual field defects [ 58 ].…”
Section: Clinical Testing and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent longitudinal studies have suggested visual acuity declines at a rate of −1.8% to −3.8% per year in RHO-RP. 138 There are several challenges to developing gene therapy for RHO-RP. While autosomal recessive IRDs may be treated by simply correcting for the absence of functional protein, dominant negative RHO variants, such as the common P23H mutation in RHO-adRP, additionally require suppression of deleterious mutant protein expression.…”
Section: Photoreceptor-localizing Genesmentioning
confidence: 99%
“…Low vision often does not develop until the third decade of life, and patients frequently avoid blindness until the eighth decade or later. Recent longitudinal studies have suggested visual acuity declines at a rate of −1.8% to −3.8% per year in RHO-RP 138…”
Section: Genes and Gene Therapiesmentioning
confidence: 99%